Pengaruh Disiplin Kerja, Motivasi Kerja, Komunikasi Kerja terhadap Kinerja Karyawan di PT Alpha Teknologi Indonesia - Andriani Andriani; Kardinah Indrianna Meutia; Nita Komala Dewi (Manajemen Kreatif Jurnal, 2025)
This research aims to test whether Work Discipline, Work Motivation and Work Communication have an effect on employee performance. The method used in this research uses quantitative methods. The population in this study were employees at PT. Alpha Technology Indonesia. The sample used in this research used a saturated sample using the Slovin formula calculation to obtain 133 respondents. Data analysis using SmartPLS 4.0 The analysis method used is descriptive analysis, validity test, reliability test, R-Square test, F-Square test and hypothesis test. The research results show that work discipline has no effect on employee performance with a t-statistic of 0.790 < 1.96, then the research results also show that work communication has no effect on employee performance, this is shown by a t-statistic value of 0.910 < 1.96 However, there is a positive and significant influence between work motivation on employee performance with a t-statistic value of 6.635 > 1.96. This shows that the greater the employee's motivation, the better the employee's performance will be